Découverte, étude et restauration de peintures murales (ca. 1400) en l’église Saint-Jean à Malines - Marjan Buyle; Anna Bergmans (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The discovery in Saint John’s church in Mechelen of the wall paintings dating from around 1400 was remarkable in more than one way. The uncovering and restoration of this well-preserved ensemble led to a thorough study of material and techniques from this era on which there had been only little research until now. The artistic quality of these two major paintings of Saint Christopher and Saint George with dragon reveal the hand of a painter experienced in monumental compositions.